THE ROHINGYA CRISIS AND INTERNATIONAL DISPLACED AGGRESSION IN INDONESIA - Shary Charlotte Henriette Pattipeilhy; Reni Windiani (Jurnal Ilmiah Hubungan Internasional, 2020)
This article seeks to analyze the social situation in Indonesia, where the conflict that occurred overseas manifested into violent actions against person or group within the country, who is considered to have a similar identity with overseas perpetrators. This pattern of violence is perpetrated against minority groups in Indonesia who have no involvement in conflict abroad. Some impacts of the Rohingya crisis in Indonesia are ranging from forced closure threat to Vihara in Medan, a demonstration on Buddhist religious symbols, beating against a Buddhist monk, and even bomb terror in Vihara. In social psychology theory, this violence is part of Freud's Defense Mechanism theory called Displacement. Furthermore, to answer why this displaced aggression can occur in Indonesia, I use Social Identity theory that the reductionist view of singular affiliation creates a gap in understanding of 'Self' and 'Other.' It then creates an intergroup bias when individuals tend to prioritize their group (in-group) compared to other groups (out-group). At last, this situation also reaffirms the concept of imagined community by Benedict Anderson.